Access and utilization of sanitation facilities in a Rural Area of Haryana, North India - Shashi Kant; Ravneet Kaur; Ayush Lohiya; Farhad Ahamed; Sumit Malhotra; Partha Haldar (Wolters Kluwer Medknow Publications, 2020)
Background: Ensuring universal access to sanitation in households is essential for public health. Objectives: The objective of the study was to assess the availability of sanitary latrine at the household level and its use at the individual level in a rural area and factors associated with availability and use of sanitary latrine. Methods: This cross-sectional study was conducted from December, 2016 to January 2017 (mention month and year) at the rural Health and Demographic Surveillance Site, Ballabgarh, in district Faridabad, Haryana, North India. A total of 16,896 households were studied. House-to-house visits were made by trained health workers who conducted interviews regarding availability and pattern of use of sanitary latrine in the household. The health worker also observed the type of sanitation facility, its functional status, availability of water, and hand-washing facility. Results: Individual household latrine (IHL) was present in 87.3% of the households. An improved sanitation facility was available in 84.8% of the households, while 15.2% of the households had unimproved or no sanitation facility. Hand-washing facility along with improved sanitation was present in 70.4% of the households. Nonavailability of latrine among socially disadvantaged communities (scheduled caste households) was significantly higher (19.4%) as compared to other castes (10.4%) (P < 0.001). A significantly higher proportion of households below poverty line (28.9%) lacked IHL as compared to those above the poverty line (11.0%) (P < 0.001). Nearly 11% of the individuals reported open defecation. Conclusion: The availability of sanitary latrines in the study area was high. Nonavailability of in-house sanitary latrine was higher among economically poor households and those belonging to socially disadvantaged communities.